Comparing Mukammal and Tikrar Methods in Qur’an Memorization Approaches: Membandingkan Metode Mukammal dan Tikrar dalam Pendekatan Menghafal Al-Qur'an - Misra Nova Dayantri; Hasan Asari; Zaini Dahlan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The effectiveness of memorizing the Qur’an is deeply influenced by the strategies employed within tahfidz institutions. Specific Background: In Indonesia, pesantren have developed various methods to support this process, notably the Mukammal and Tikrar methods, each with distinct pedagogical characteristics. Knowledge Gap: However, empirical comparisons of these two methods across different institutional contexts remain limited, hindering data-driven decisions in tahfidz curriculum design. Aims: This study aims to compare the effectiveness of the Mukammal and Tikrar methods in two pesantren—Pondok Pesantren Ulumul Qur’an Stabat and Pesantren Modern Muhammadiyah Kwala Madu Langkat. Results: Using a qualitative case study approach involving observation, in-depth interviews, and documentation, findings reveal that the Mukammal method emphasizes structured murajaah and accuracy, whereas the Tikrar method prioritizes intensive, flexible repetition for accelerated memorization. Novelty: The research presents a comparative perspective grounded in real institutional practices, showcasing how each method aligns with the unique needs and characteristics of santri. Implications: The study offers practical insights for educational institutions in selecting or adapting Qur’an memorization strategies tailored to their pedagogical context. Highlights: Highlights a comparison between two widely used tahfidz methods. Emphasizes the importance of aligning methods with santri characteristics. Offers practical insights for improving memorization programs in pesantren. Keywords: Qur’an Memorization, Mukammal Method, Tikrar Method, Islamic Education, Tahfidz Strategy